Pharmacological Validation of ASIC1a as a Druggable Target for Neuroprotection in Cerebral Ischemia Using an Intravenously Available Small Molecule Inhibitor - Qi, Xin; Lu, Jian-Fei; Huang, Zi-Yue; Liu, Yi-Jun; Cai, Lu-Bing; Wen, Xin-Lan; Song, Xing-Lei; Xiong, Jian; Sun, Pei-Yi; Zhang, Hao; Zhang, Ting-Ting; Zhao, Xuan; et al. (Frontiers in Pharmacology, 2022)
Acidosis is a hallmark of ischemic stroke and a promising neuroprotective target for preventing neuronal injury. Previously, genetic manipulations showed that blockade of acid-sensing ion channel 1a (ASIC1a)-mediated acidotoxicity could dramatically alleviate the volume of brain infarct and restore neurological function after cerebral ischemia. However, few pharmacological candidates have been identified to exhibit efficacy on ischemic stroke through inhibition of ASIC1a. In this work, we examined the ability of a toxin-inspired compound 5b (C5b), previously found to effectively inhibit ASIC1a in vitro, to exert protective effects in animal models of ischemic stroke in vivo. We found that C5b exerts significant neuroprotective effects not only in acid-induced neuronal death in vitro but also ischemic brain injury in vivo, suggesting that ASIC1a is a druggable target for therapeutic development. More importantly, C5b is able to cross the blood brain barrier and significantly reduce brain infarct volume when administered intravenously in the ischemic animal model, highlighting its systemic availability for therapies against neurodegeneration due to acidotoxicity. Together, our data demonstrate that C5b is a promising lead compound for neuroprotection through inhibiting ASIC1a, which warrants further translational studies.